Fungus-feeding thrips from Australia in the worldwide genus Hoplandrothrips (Thysanoptera, Phlaeothripinae) - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2013)
From Australia, 16 species of Hoplandrothrips are here recorded, of which 11 are newly described. An illustrated key is provided to 15 species, but Phloeothrips leai Karny cannot at present be recognised from its description. The generic relationships between Hoplandrothrips, Hoplothrips and some other Phlaeothripinae that live on freshly dead branches are briefly discussed.